Physical and mechanical properties of LDPE incorporated with different starch sources - Kormin, Shaharuddin; Kormin, Faridah; Hossen Beg, Mohammad Dalour; Mat Piah, Mohd Bijarimi (IOP Publishing, 2017)
In this study it was investigated the incorporation of different starches, such as sago starch, corn starch, potato starch, tapioca starch and wheat starch, in low-density polyethylene matrix (LDPE) to enhanced mechanical properties and to obtain partially biodegradable product with the aim to reduce the plastics wastes in the environment. For comparison, virgin LDPE, LDPE with different sources of starch blends were prepared and characterized under the same conditions. The starches were mixed to the LDPE using a twin screw extruder to guarantee the homogeneity of the formulations. The compound were shaping processed by injection moulding. The characterization of those compounds was done by physical (density, MFI), mechanical (Universal tensile machine). The addition of starch to LDPE reduced the MFI values, the tensile strength, elongation at break and impact strength, whereas the elastic modulus, flexural modulus and flexural strength increased. LDPE/SS show the good mechanical behavior compared to other formulation. The physical and mechanical properties were evident when 5 and 30 wt% were added. Water uptake increased with increased starch content and immersion time. The time taken for the composites to equilibrate was about one month even when they were immersed completely in water.